2021
DOI: 10.3390/horticulturae8010010
|View full text |Cite
|
Sign up to set email alerts
|

Light Spectrum Variably Affects the Acclimatization of Grafted Watermelon Seedlings While Maintaining Fruit Quality

Abstract: In many countries of Europe and Eastern Asia, watermelon production is mainly based on the use of grafted seedlings. Upon grafting, seedlings undergo a period of healing where artificial lighting is provided by light-emitting diodes in controlled chambers in order to accelerate and improve the healing process. The objective of our study was to test the effect of light quality on the final product (i.e., seedlings ready for transplanting) in the nursery, as well as to evaluate the possible implications on fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
1
3
1
1
Order By: Relevance
“…From DAT 0, stems were significantly narrower under the influence of FL and B, an effect which carried on up to DAT 14 (Figure 1A). This is in accordance with a previous study of our group which showed that monochromatic B limited the stem diameter of acclimatized watermelon seedlings compared to red-containing LEDs [14], while FL also induced narrow stem development of the final product (unpublished observation). Stem diameter has been proposed and has widely been used as an indicator of seedling quality in vegetable species, such as tomato, pepper, eggplant [15], cucumber [16], and watermelon [17].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…From DAT 0, stems were significantly narrower under the influence of FL and B, an effect which carried on up to DAT 14 (Figure 1A). This is in accordance with a previous study of our group which showed that monochromatic B limited the stem diameter of acclimatized watermelon seedlings compared to red-containing LEDs [14], while FL also induced narrow stem development of the final product (unpublished observation). Stem diameter has been proposed and has widely been used as an indicator of seedling quality in vegetable species, such as tomato, pepper, eggplant [15], cucumber [16], and watermelon [17].…”
Section: Resultssupporting
confidence: 93%
“…Compared to 2018, our 2021 watermelons produced about 30% greater total phenolics (0.12-0.15 mg/g in 2018 versus 0.20-0.23 mg/g in 2021) and about 50% greater antioxidant capacity displayed by FRAP (35-40 µg/g in 2018 versus 76-87 µg/g in 2021), pointing to the harsh climatic conditions which acted positively towards watermelon fruit quality. In the same study in 2018, proper morphology, root development, photosynthesis, and high fruit quality were noted on grafted watermelon plants that were treated with blue + far-red LED light during the healing stage [14].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This compound plays a significant role against prostate cancer [26]. In another experiment [27], watermelon fruits in Greece, in 2018, which had milder summer temperatures, showed lower total phenolic content and antioxidant activity compared those in the present study. This was also observed in another study of our group which resulted in greater fruit quality in 2021 crops compared with that of 2018 crops [28].…”
Section: Resultscontrasting
confidence: 46%
“…This compound plays a significant role against prostate cancer [26]. In another experiment [27], watermelon fruits in Greece, in 2018, which had milder summer temperatures, showed lower total phenolic content and Strikingly, Optimum plants reached 82%, 93%, and 100% of their total yield from flowers that bloomed on DAT 30, DAT 32, and DAT 34, compared to DAT 36, respectively. The respective percentages for Acceptable plants were 36%, 73%, and 94%.…”
Section: Resultsmentioning
confidence: 99%